Symptom prevalence, severity, distress and management among patients with chronic diseases - Fatima ALHosni; Mohammad Al Qadire; Omar Al Omari; Huda Al Raqaishi; Atika Khalaf (BMC, 2023)
Abstract Background Advanced knowledge, technology, and treatment approaches resulted in longer survival rates for patients suffering from chronic diseases. However, symptoms of these diseases persist and affect the individual's entire life and normal functioning. Aim To assess symptoms prevalence, severity, distress, and management among patients with chronic obstructive pulmonary diseases (COPD), chronic heart failure (CHF), and end-stage renal disease (ESRD) in Oman. Design A descriptive cross-sectional design was used. Sample and settings The study sample comprised 340 participants who were recruited between May and December 2021 from two referral hospitals and one large dialysis unit in the Sultanate of Oman, Muscat Governate using a convenience sampling technique. Results The highly prevalent symptoms among patients with selected chronic diseases were lack of energy (60.9%), pain (57.4%), numbness (53.2%), difficulty sleeping (49.4%), and shortness of breath (45.9%). The most severe symptoms were shortness of breath (53.2%), problems with urination (51.9%), constipation (50.8%), difficulty sleeping (49.7%), and pain (46.2%). The symptom "problems with sexual interests or activity" was found to be the most frequently occurring and highly distressing symptom out of all reported symptoms. Conclusions The current study's findings showed that symptoms were prevalent and that some symptoms were frequent, severe, and highly distressing. In addition, patients perceived symptom treatment as inadequate. Psychological symptoms received less treatment attention compared with physical symptoms. One of the mainstays for managing symptoms can be the introduction of palliative care. Providing palliative care to these patients can alleviate their suffering and improve their quality of life. In addition, designing chronic disease self-management programmes can make a difference in patients' life.